Over produktieve en onproduktieve arbeid. - Marx, Karl; Kümmel, G.; Löhlein, G.; Bischoff, Joachim; Ganzmann, H. (Nijmegen : SUN, 1970)
Bibliotheek François Vercammen
Nederlands
Monografie
Keywords: Marx, Karl; productiviteit